Modified Droop Method Based on Master Current Control for Parallel-Connected DC-DC Boost Converters - Muamer M. Shebani; Tariq Iqbal; John E. Quaicoe (Journal of Electrical and Computer Engineering)
Load current sharing between parallel-connected DC-DC boost converters is very important for system reliability. This paper proposes a modified droop method based on master current control for parallel-connected DC-DC boost converters. The modified droop method uses an algorithm for parallel-connected DC-DC boost converters to adaptively adjust the reference voltage for each converter according to the load regulation characteristics of the droop method. Unlike the conventional droop method, the current feedback signal (master current) for one of the parallel-connected converters is used in the inner loop controller for all converters to avoid any differences in the time delay of the control loops for the parallel-connected converters. The algorithm ensures that the load current sharing is identical to the load regulation characteristics of the droop method. The proposed algorithm is tested with a mismatch in the parameters of the parallel converters. The effectiveness of the proposed algorithm is verified using Matlab/Simulink simulation.